2019
DOI: 10.1177/1071100719891411
|View full text |Cite
|
Sign up to set email alerts
|

3D, Weightbearing Topographical Study of Periprosthetic Cysts and Alignment in Total Ankle Replacement

Abstract: Background: We investigated the association between hindfoot residual malalignment assessed on weightbearing computed tomography (WBCT) images and the development of periprosthetic cysts (PPCs) after total ankle replacement (TAR). We hypothesized that PPCs would be found predominantly medially in the varus configuration and laterally in the valgus configuration. Methods: Cases of primary TAR with available WBCT imaging of the ankle were included in this retrospective study. The location of the PPC was marked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 47 publications
0
28
1
Order By: Relevance
“…Three-dimensional biometrics will bring us more insights about the effect of corrective foot and ankle surgeries (calcaneus and supramalleolar osteotomies, triple arthrodesis) on the lower limb or for patients who experienced complications (pain, accelerated degenerative process) that are not explained solely by the condition of the ankle joint (periprosthetic cysts in ankle replacement). 10 Beyond a better understanding of alignment (including rotation) in basic science, the ultimate goal remains to detect and/or to monitor patients who are at risk to decompensate after additional elective surgeries of the lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional biometrics will bring us more insights about the effect of corrective foot and ankle surgeries (calcaneus and supramalleolar osteotomies, triple arthrodesis) on the lower limb or for patients who experienced complications (pain, accelerated degenerative process) that are not explained solely by the condition of the ankle joint (periprosthetic cysts in ankle replacement). 10 Beyond a better understanding of alignment (including rotation) in basic science, the ultimate goal remains to detect and/or to monitor patients who are at risk to decompensate after additional elective surgeries of the lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that progressive periprosthetic cysts lead to implant instability and poor implant survivorship. 20,26,27,30 One potential cause for the increased incidence of progressive cyst formation for the STAR TAR is that it uses a mobile-bearing polyethylene liner that is susceptible to medial edge-loading and polyethylene wear if alignment and tracking are not optimal. 45 We chose to elucidate the incidence of progressive cyst as an important complication because these are the ones that should be closely monitored with serial radiographs and potentially bone grafted to prevent implant compromise.…”
Section: Discussionmentioning
confidence: 99%
“…The total cystic volume was positively correlated with residual malalignment, measured by the absolute FAO values, with the varus alignment presenting a more medially positioned cyst and the valgus alignment a laterally positioned cyst. 48…”
Section: Foot and Anklementioning
confidence: 99%